(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
The International Criminal Court (ICC), established under the Rome Statute in 2002, has played a central role in the global fight against impunity for the gravest international crimes. This research analyzes the efficacy of the ICC in addressing international crimes in the 21st century, focusing on its successes, limitations, and ongoing challenges. By reviewing key cases and investigations, the study explores the ICC’s impact on international criminal law, its role in deterring international crimes, and its influence on the domestication of criminal law in member states. The research also addresses critical obstacles to the Court’s effectiveness, including the lack of state cooperation, political resistance from powerful non-signatory countries, and its limited number of convictions. Through a comprehensive evaluation, this paper aims to provide recommendations for enhancing the ICC’s capacity to deliver justice and promote accountability in an increasingly complex global landscape..